Perancangan Aplikasi Optimalisasi Inventori Berbasis Web pada Best Store. - Justin Lius; Desi Arisandi (Fakultas Teknologi Informasi Universitas Tarumanagara, 2025)
The rapid development of technology encourages various business sectors to adopt digital solutions to improve operational efficiency. One important aspect of business management is inventory management, which is often a big challenge when done manually. Best Store, a business that sells electrical appliances and daily necessities, faced a problem in managing stock items that were still using manual methods, such as recording using books and Excel. This causes various problems, such as recording errors, data loss, and ineffective stock monitoring.To overcome these problems, this research designs a web-based application that can optimize inventory management at Best Store. This application is designed using the Software Development Life Cycle (SDLC) methodology, which includes system analysis, design, development, implementation, testing, and system maintenance. In addition, this application uses the UML model to facilitate object-oriented system design, and is equipped with real-time stock monitoring features, transaction management, and reorder point settings.